Isolation and quantification of pinitol in Argyrolobium roseum plant, by 1H-NMR - Neha Sharma; Mahendra K. Verma; Devinder K. Gupta; Naresh K. Satti; Ravi K. Khajuria (Journal of Saudi Chemical Society)
Chemical investigations on ethanolic extract of Argyrolobium roseum led to the isolation of Pinitol as the major constituent of the plant. Pinitol is chemically known as 3-O-methyl-D-Chiro-inositol and has been found to possess anti-diabetic activity. It helps in the regeneration of beta cells, present in the areas of the pancreas called as islets – of Langerhans. These cells make and release insulin, a hormone which controls the level of glucose in the blood. Pinitol was isolated from the ethanolic extract of the plant and a sensitive & reliable method, based on Proton Nuclear Magnetic Resonance (PNMR), was developed and used as an analytical tool for quantification and identification of this relatively UV insensitive compound in the alcoholic extract of the plant. The method involves the use of pyrazinamide (an anti-tuberculosis drug), as a reference. Validation of the method was carried out by preparing a known concentration of an artificial mixture of pinitol and pyrazinamide. The recovery of pinitol in the mixture was in the range of 98.5–101.3%. Pinitol in pure form was isolated from the ethanolic extract of A. roseum by repeated column chromatography over silica gel followed by crystallization in methanol. Pinitol isolated from the plant was identified on the basis of 1H-NMR, 13C-NMR, DEPT (45°, 90° and 135°) experiments and mass spectral data. The method was successfully applied for the quantitation of pinitol in various extracts of the said plant.